2001
DOI: 10.3354/dao047063
|View full text |Cite
|
Sign up to set email alerts
|

Bonamia exitiosus n.sp. (Haplosporidia) infecting flat oysters Ostrea chilensis in New Zealand

Abstract: Bonamia sp. is a pathogenic parasite that occurs in the haemocytes of dredge oysters Ostrea chilensis Philippi in New Zealand. Ultrastructurally it resembles other haplosporidians in the possession of haplosporosomes, haplosporogenesis, persistence of mitotic microtubules during interphase and of the nuclear envelope during mitosis, and occurrence of a diplokaryotic or multi-nucleate plasmodial stage. Another stage containing a large vacuole derived from enlargement of 1 or more mitochondria has not previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 32 publications
2
100
1
Order By: Relevance
“…Dis Aquat Org 89: [79][80][81][82][83][84][85] 2010 Bonamia exitiosa infects Ostrea chilensis in New Zealand (Hine et al 2001) and O. angasi in Australia (Corbeil et al 2006) and has been recently reported in O. edulis in Spain (Abollo et al 2008). B. roughleyi, previously called Mikrocytos roughleyi, infects Saccostrea glomerata in southeast Australia (Farley et al 1988).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 2 more Smart Citations
“…Dis Aquat Org 89: [79][80][81][82][83][84][85] 2010 Bonamia exitiosa infects Ostrea chilensis in New Zealand (Hine et al 2001) and O. angasi in Australia (Corbeil et al 2006) and has been recently reported in O. edulis in Spain (Abollo et al 2008). B. roughleyi, previously called Mikrocytos roughleyi, infects Saccostrea glomerata in southeast Australia (Farley et al 1988).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…B. ostreae (Pichot et al 1980) occurs naturally in O. edulis L. (Grizel et al 1983). Bonamia exitiosa infects Ostrea chilensis in New Zealand (Hine et al 2001) and O. angasi in Australia (Corbeil et al 2006) (Farley et al 1988). B. perspora is a newly described protozoan species found in Ostreola equestris (North Carolina, USA) and represents the first Bonamia species producing a typical haplosporidian spore (Carnegie et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical measures that have had some success include: (1) introduction of new or resistant species and varying the sources of spat to maintain the same level of economic activity (Grizel 1983, Grizel and Héral 1991, Ewart and Ford 1993, McKindsey et al 2007, Padilla 2010, Castinel et al 2015; (2) chemical or physical solutions such as water treatment, animal purification, immunostimulants, penicillin, active clay, hydrogen peroxide, and coagulants to prevent or limit disease (Di Salvo et al 1978, Matsuyama 1999, Mydlarz et al 2006; and (3) prevention measures such as monitoring and surveillance systems, quarantine and prevention of oyster movements to contain the disease, awareness and reporting by the industry, and risk assessment (Matsuyama 1999, Hine et al 2001, Murray et al 2012, Paul-Pont et al 2014, Castinel et al 2015. Organizational responses (e.g., state aid, mutual funds, diversification strategies, private insurance, inventories, and savings) occur at both individual and collective levels (Grizel 1983, Le Bihan et al 2013, Lupo et al 2014.…”
Section: Societal Responses To Mass Mortalities Of Bivalves Issuesmentioning
confidence: 99%
“…Bonamia exitiosus, morphologically similar to B. ostreae, is pathogenic to the dredge oyster Ostrea chilensis in New Zealand (Hine 1991, Hine et al 2001. Both species of Bonamia were tentatively considered haplosporidians despite the apparent absence of sporulation during their life cycles (Pichot et al 1980, Hine & Wesney 1992, Hine et al 2001) and molecular evidence has recently confirmed their inclusion in the phylum Haplosporidia (Carnegie et al 2000.Histological examination of cultured abalone from a New Zealand aquaculture facility experiencing mortalities suggested the presence of a haplosporidian parasite, although no spores were observed . Molecular genetic analysis was performed using SSU rDNA obtained from infected abalone to further characterize this organism.…”
mentioning
confidence: 99%